PERENCANAAN DISTRIBUSI AIR BERSIH DI KECAMATAN HULU PALIK KABUPATEN BENGKULU UTARA DENGAN SOFTWARE WATERCAD 8i - Rama, Alri Ananda Waskita; Sholichin, Moh; Fidari, Jadfan Sidqi (Fakultas Teknik, Universitas Brawijaya, 2023)
Over time, the need for clean water is increasing. Changes in land use as well as population growth every year further encourage the increase in the need for water. Clean water is one of the main needs in fulfilling water in Indonesia. So water supply needs to be a top priority in each region. Hulu Palik District is part of North Bengkulu Regency, the area has a large and continuous supply of clean water throughout the year at the Batu Layang spring. However, the distribution of clean water is still not good. Thus, an effort is needed to optimize the utilization of water availability by planning clean water distribution of network system so the benefits can be felt by the people of Hulu Palik District. This study is planning a new network with a useful life of up to 2041, so it is required to projection the population and determine discharge of water demand until 2041. Analysis of the hydraulics aspects of the pipe pressure (0.5 atm -10 atm), velocity (0.1 l/s – 2.5 l/s), hydraulic gradient (0 m/km -15 m/km), residual chlorine (0.3 mg – 0.5 mg), and calculation of pipe budget plan referring to Unit Price North Bengkulu Regency work using WaterCAD V8i Software. Based on the budget plan, can calculate the Economic Analysis to determine the price of water. In 2041 the population of the service area is 14341 people with an average daily water requirement of 22.90 l/s, with a domestic demand of 16.6 l/s, non-domestic demand of 2.49 l/s and a water loss factor of 3.82 l/s. At peak hours, the water demand in 2041 is 35.73 l/s and the maximum daily demand is 26.34 l/s. The design feasibility index includes pressure, velocity, residual chlorine hydraulic slope and economic feasibility. Based on research from analysis of feasibility index, clean water distribution network planning for Hulu Palik District was declared feasible. The required budget plan is IDR 11,692,745.64. Economic analysis is carried out using an interest rate of 3.5% and a useful life of up to 2041, a water price of Rp. 3,947.38/m3 is obtained in terms of the parameters of BCT, NPV, IRR and sensitivity analysis.Kecamatan Hulu Palik merupakan bagian dari Kabupaten Bengkulu Utara, daerah tersebut memiliki ketersediaan air bersih yang besar dan kontinu sepanjang tahun pada mata air Batu Layang. Namun, pendistribusian air bersih masih kurang baik. Sehingga, diperlukan suatu upaya untuk mengoptimalkan pemanfaatan ketersediaan air dengan merencanakan sistem jaringan distribusi air bersih yang nantinya dapat dirasakan manfaatnya bagi masyarakat Kecamatan Hulu Palik. Studi ini melakukan perencanaan jaringan baru dengan usia guna hingga tahun 2041, sehingga perlu dilakukan proyeksi jumlah penduduk dan mengetahui debit kebutuhan air hingga tahun 2041. Analisa terhadap aspek hidrolika pada jaringan perpipaan, kualitas air terhadap sisa klorin dan perhitungan RAB pipa yang mengacu pada Harga Satuan Pekerjaan Kabupaten Bengkulu Utara menggunakan Software WaterCAD V8i. Berdasarkan RAB, dapat menghitung Analisa Ekonomi hingga penentuan harga air.Pada tahun 2041 jumlah penduduk daerah layanan sebanyak 14341 jiwa dengan kebutuhan air harian rerata sebesar 22.90 lt/dt. Indeks kelayakan perencanaan meliputi tekanan, kecepatan, kemiringan hidrolis sisa klorin dan kelayakan ekonomi. Berdasarkan hasil analisa terhadap indeks kelayakan, perencanaan jaringan distribusi air bersih Kecamatan Hulu Palik dinyatakan layak. Rencana anggaran biaya yang diperlukan sebesar Rp 11,692,745,64. Analisa Ekonomi dilakukan dengan menggunakan suku bunga sebesar 3.5% dan usia guna hingga tahun 2041, didapat harga air sebesar Rp 3,947.38/m3.